The Autocatalytic Sprawl of Pseudorational Mastery - Ulf Martin (Review of Capital as Power, 2019)
According to Jonathan Nitzan and Shimshon Bichler (2009), capital is not an economic quantity, but a mode of power. Their fundamental thesis could be summarized as follows: capital is power quantified in monetary terms. But what do we do when we quantify? What is the nature of money in a capitalist society? Indeed, what is power? In the following, we try to develop a co ncept of power as the ability of persons to create particular formations against resi stance. The kinds of formations persons can think of depend on the society they live in, which can be identified by what Cornelius Castoriadis called its social imag inary significations (SIS). The core SIS of capitalism is rational mastery operating with computational rationality. Computational rationality in turn rests on a parti cular understanding of how signification works: it works through operational symbolism , as theorized by Sybille Krämer in analyzing the philosophy of Leibniz. When the concept of the SIS of modern rationality was developed in the 1950s and 1960s, bureau cracy was seen as the main organizational mode of rational mastery. We argue that there are two modes of rational mastery, capitalization and bureaucratization, that interact with each other in capitalist society. The paper concludes with deliberat ions on the future of rational mastery and possible ways out.
Keywords: 330; autonomy; autocatalytic; sprawl; bureaucratization; capitalization; rationality; power; signification; symbolism